Lignin nanoparticles: New insights for a sustainable agriculture - Pereira, Anderson do Espirito Santo [UNESP]; Luiz de Oliveira, Jhones [UNESP]; Maira Savassa, Susilaine [UNESP]; Barbara Rogério, Carolina [UNESP]; Araujo de Medeiros, Gerson [UNESP]; Fraceto, Leonardo Fernandes [UNESP] (Elsevier, 2022)
Global agriculture is looking for new agri-tech revolutions not only due to the ever-growing need for increased food production but also to protect the environment from the harmful impacts of many of the current practices in the field. In this context, nanotechnology has emerged as a platform that has the potential to transform the entire food chain, making agriculture more resilient and sustainable. For example, the use of nano-scale carriers for the development of nanopesticides can improve the biological activity of synthetic or natural (botanical) pesticides while reducing their adverse effects on the environment. Lignin is one of the most abundant biopolymers on Earth, with a chemical structure that can vary depending on the lignin source. With its many functional groups, lignin can provide several useful functionalities including ultraviolet protection and antioxidant and antimicrobial activities. These properties have led to the use of lignin for the development of nanocarriers. Nanoformulations using lignin represent an opportunity to use this material, which is currently an agricultural byproduct of low value, to produce pesticide formulations in an environmentally sustainable way. This review aims to explore the potential applications of lignin nanoparticles in the agriculture sector, highlighting processes used for lignin extraction, methodologies for nanoparticle production, analysis of biological activity, and emerging applications relevant to sustainable agriculture.
Keywords: Agriculture; Bioeconomy; Green nanotechnology; Nanoparticles; Sustainability